Transcervical access in acute ischemic stroke. (7th November 2013) - Jadhav, Ashutosh P; Ribo, Marc; Grandhi, Ramesh; Linares, Guillermo; Aghaebrahim, Amin; Jovin, Tudor G; Jankowitz, Brian T
Abstract : Background: Large vessel occlusive disease portends a poor prognosis unless recanalization is rapidly achieved. Endovascular treatment is typically performed via a transfemoral approach, but catheterization of the occluded vessel can be problematic in cases of extensive vessel tortuosity. Methods: A retrospective review of a prospectively maintained database identified 7 patients who underwent acute endovascular reperfusion therapy via transcervical approach. Results: We identified 7 patients. Admission NIHSS ranged from 8–27 and recanalization occurred between 7–49 min of carotid access. Prior to carotid access, 20–90 min were spent attempting target vessel catheterization via the transfemoral approach. All occlusions were in the left MCA. In 87.5% of patient, TICI2b/3 recanalization was achieved. Neck hematoma formation occurred in one case requiring elective intubation. At 2 months followup, all patients had survived with mRS 0–4 except for one patient who had a large infarct despite recanalization. Conclusions: Transcervical access for acute ischemic stroke leads to rapid and high quality recanalization. Future studies will focus on improved hemostasis and early identification of patients who would benefit the most from direct carotid access for acute stroke.